Role of Sports Injuries Rehabilitation Weight Lift and Impact of Enkephalin Levels to Reduce Low Back Pain - Hamidi , Ali Khayon Tarish; Jassim, Ahmed Hatem Ahmed (Jurnal Porkes, 2025)
Low back pain is a common injury among weightlifters, often affecting their athletic performance and training capacity. This study aimed to investigate the effect of rehabilitation programs on alleviating low back pain by measuring enkephalin levels, a biological compound with analgesic properties. This study relied on an experimental approach to test the effect of sports rehabilitation programs on low back pain in weightlifters. This was achieved by assessing blood enkephalin levels, lumbar muscle strength, and pain levels before and after implementing the rehabilitation programs. The analysis was assisted using SPSS version 26. The results showed that rehabilitation of weightlifting injuries and the impact of enkephalin levels had a significant effect in reducing lower back pain (p < 0.000). The outcomes indicated a tremendous impact of rehabilitation on enhancing muscle electricity and lowering ache, with enkephalin levels having a massive impact on ache comfort and growing performance. Conclusion, the rehabilitation program implemented as a treatment plan for chronic low back pain in weightlifters, especially those with mechanical injuries, is effective.